The link between tinnitus and menstrual cycle disorders in premenopausal women - Margaret Zuriekat; Baeth Al-Rawashdeh; Amani Nanah; Manar Nanah; Asma S. Basha (Scientific Reports)
Abstract This cross-sectional study aimed to explore the association between tinnitus and menstrual cycle disorders in premenopausal women. A total of 558 participants completed a comprehensive questionnaire covering demographics, tinnitus, and gynecological/obstetric history. The analysis investigated the correlation between tinnitus and various menstrual disorders, including dysmenorrhea (primary, secondary, or premenstrual syndrome), as well as different menstrual cycle patterns (regular, hypomenorrhea, menorrhagia, oligomenorrhea, or polymenorrhea). Among the participants, 33% reported experiencing tinnitus, with 74.4% experiencing dysmenorrhea. The most prevalent pathological menstrual pattern was menorrhagia (20%), followed by hypomenorrhea (11.11%). The results revealed a significant increase in tinnitus among premenopausal women with secondary dysmenorrhea (p value < 0.001) or menorrhagia (p value < 0.002) compared with those without tinnitus. Adjustment for confounding variables such as age, income, and psychological health problems did not alter the significant correlations between tinnitus and secondary dysmenorrhea and menorrhagia. Further research is needed to elucidate the nature of this relationship and its underlying mechanisms. Both tinnitus and menstrual disorders can have substantial impacts on the well-being of affected women, and a deeper understanding of these issues could pave the way for improvements in their health care.